CW-EPR spectra of P1 centers in HPHT diamond in the vicinity of Rabi resonance: possible standard for B1 evaluation in EPR and DNP enhanced NMR spectroscopies - B. Rakvin; D. Carić; M. Kveder (Journal of Magnetic Resonance Open, 2022)
Synthetic commercial type-IIa diamond crystal containing low concentration of P1 (Ns0) centers ([Ns0] <1ppm) was examined as a possible calibration standard for evaluating microwave magnetic field intensity (B1) in the spectrometer cavity. The reliability of this standard was experimentally and theoretically tested by employing two different types of microwave cavities with different distributions of B1 values. The procedure relies on the ordinary continuous wave electron paramagnetic resonance (CW-EPR) with magnetic field modulation (ωrf/2π=100 kHz) applied under the regime of the microwave power (PMW) saturation of the out-of-phase first harmonic signal. The power saturation procedure for PMW∼B11/2 was analyzed with respect to the change of spectral lineshape when Rabi frequency (ω1=γB1, γis the electron gyromagnetic ratio) approaches to ωrf. The phenomenon of the inversion of sideband lines while passing the Rabi resonance condition (ω1=ωrf) was analyzed. In specific, from the simulation of the experimental lineshapes in the close vicinity of Rabi resonance (ω1≈ωrf) the correspondingB1 can be assigned. For the chosen diamond crystal low value of B1≈3.6µT at Rabi resonance was determined what makes it a convenient standard for DNP enhanced NMR spectroscopy which requires relatively small B1.